The Re-Establishment Decision In Turkish Armed Forces - Karasu, Şemsettin (My University, 2008)
Soğuk Savaş dönemini sona erdiren SSCB’nin yıkılışı ülkelerin ordularını küçültme ve yenilemesi için dönüm noktasıdır. Soğuk Savaş’tan sonra tehdit algılaması değişti ve bu da pek çok Avrupa ve NATO ülkelerinin askere alma sistemlerini sorgulamasına neden oldu. Bunun neticesi olarak Fransa, İtalya, İspanya, Portekiz, Belçika ve Hollanda askere alma sistemlerini değiştirdiler. Coğrafi konumu, eski SSCB ile sınır komşusu olması, çatışmaların yoğun olarak yaşandığı Kafkaslar, Ortadoğu ve Balkanlar’ın ortasında yer alması Türkiye’yi güçlü bir orduya sahip olmaya zorlamıştır. Kurulduğu günden beri Türkiye zorunlu askerlik sistemini uygulamaktadır ancak 1990’lardan sonra silahlı kuvvetlerdeki profesyonel sayısının artması için çalışmalar yapılmıştır. Şayet tam profesyonel bir orduya geçiş süreci takip edilecekse Milli Savunma Bakanlığı’nın karşılaşacağı ilk sorun yeterli sayıda başvurunun olup olmayacağıdır. Bu nedenle bu tezde askere yazılma kararı ve askere yazılmak isteyenlerin kararlarını etkileyen faktörler bir anket aracılığıyla ampirik olarak araştırılmıştır. Genel bulgular yaş, eğitim seviyesi, aile özellikleri, iş durumu ve yaşanılan coğrafi bölgenin askere yazılma kararını etkilediğini göstermektedir.

The collapse of the USSR that brought the cold war era to an end is the turning point for countries to downsize and renew their armies. After the Cold War, the perception of threat has also changed which in turn has led many European and NATO countries to question their conscription systems. As a result of that France, Italy, Spain, Portugal, Belgium and the Netherlands changed their conscription systems. Turkey’s geopolitical position, having border with former USSR and being located at the crossroads of Caucasus, Middle East and the Balkans where the conflicts are intense, has forced the country to have a strong army. Turkey has been implementing conscription system since its foundation but after 1990s efforts have been made to increase the number of professionals in the armed forces. The very first problem Ministry of Defense would face is to meet required number of re-enlistment applications if a transformation toward a professional army to be followed. So in this thesis, the re-enlistment decision and the characteristic of individuals who would like to enlist are investigated and the factors influencing the re-enlistment decisions are aimed to be empirically determined by help of a questionnaire. General findings suggest that age, income, education level, family backgrounds, employment and region affect the re-enlistment decision.
Keywords: Türk Silahlı Kuvvetleri; Zorunlu Askerlik